CMOS : circuit design, layout, and simulation - Baker, R. Jacob, 1964- (IEEE Press ; Wiley, 2019)
"The third edition of CMOS: Circuit Design, Layout, and Simulation continues to cover the practical design of both analog and digital integrated circuits, offering a vital, contemporary view of a wide range of analog/digital circuit blocks, the BSIM model, data converter architectures, and much more"--